Addressing sustainable urban flood risk: reviewing the role and scope of theoretical models and policies - Gabriele Oneto; Maria Canepa (Water Policy, 2023)
Contemporary adaptation to urban flooding is based on risk management. Urban planners have both an active role in studying cities and a supportive role in helping to define policies. From 33 case studies, this review tries to give insight into how flood risk management fares in confronting international directives on disaster reduction and sustainability, by defining seven sustainability performance criteria. Most studies try to maximize the acceptability and feasibility of implementing solutions in cities (63.6%) and the revision of existing building codes and plans (51.5%), while fewer try to test existing urban practices for weak points (27.3%). Analyses do not fully consider urban habitats as holistic and complex systems, as citizen awareness (27.3%), costs (21.2%), and biodiversity (24.2%) are some of the least recurring and intersecting themes. The main findings should help planners define new lines of action on urban flooding and consider alternative aspects in their frameworks. HIGHLIGHTS Contextuality is the most effective measure for the acceptability of LID solutions.; The sustainability of flood management depends on the scale and objective.; Streamlining the implementation of existing LID solutions should precede new ones.; Conceptual models should bridge the scale gap and empower stakeholders.; New frameworks should cover both physical and socio-economical vulnerabilities.;